Takhrij and Syarah Hadith of Agrotechnology: Fertilization of the Dead Soil - Naufal Muhammad FilgoSeprianza; Wahyudin Yusidah; Salamet Ginandjar (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet. About soil enrichment. This research method is qualitative through the approach of takhrij and sharah hadith with agrotechnological analysis. The result and discussion of this research is that soil enrichment is recommended by the Prophet Muhammad, and continues to grow and be useful until now. The conclusion of this research is takhrij and syarah hadith of the Prophet. Regarding soil fertility, it is very useful and has various ways, one of which is the use of biological fertilizers.